EFEKTIVITAS PEMBELAJARAN MELALUI PEMBELAJARAN KOOPERATIF TIPE TGT BERBANTUAN ALAT PERAGA DI KELAS VI SD METHODIST-12 MEDAN PADA KOMPETENSI DASAR LUAS BANGUN DATAR SEDERHANA - Silaban, Patri Janson (Jurnal Ilmiah Aquinas, 2019)
The problem in this study are: (1) teachers use teacher-centered approach to the dominance of expository / lecture, (2) the growing culture through books memorizing formulas without any prior explanation, (3) learning-centered book, (4) lack of methods / media / learning strategies, (5) the dominant cognitive learning (knowledge), (6) students are not motivated in the learning of mathematics, and (7) lack of understanding of students' mathematical abilities of the subject matter of mathematics. The purpose of this study is determine the effectiveness of the student. Formulation of the problem in this study, namely: how the effectiveness of the student?Type of research is action research through cooperative learning TGT aided props as the main target. Where this study seeks to describe the use of cooperative learning TGT props aided in increasing the motivation and ability of students' mathematical understanding through cooperative learning TGT props aided in mathematics in Class VI Elementary School Methodist-12 of Medan. The subjects were students of class VI was 50 of which were 26 men and 24 women in Elementary School Methodist-12 of Medan. Determination of this class is taken based on the observation of the class that will be examined and advice from the principal. Formal object through cooperative learning TGT aided props.Learning effectiveness of students has increased from an average grade 62.48% at the cycle I to 76.04% in the cycle II and become 88.29% in the cycle III. Thus, it can be concluded that through cooperative learning TGT aided props can increase motivation and understanding of students' mathematical abilities in cognitive, affective and psychomotor widely on the subject of flat wake in Class VI Elementary School Methodist-12 of Medan.